1975
DOI: 10.1083/jcb.64.2.289
|View full text |Cite
|
Sign up to set email alerts
|

Actin filaments in the acrosomal reaction of Limulus sperm. Motion generated by alterations in the packing of the filaments.

Abstract: When Limulus sperm are induced to undergo the acrosomal reaction, a process, 50 am in length, is generated in a few seconds. This process rotates as it elongates; thus the acrosomal process literally screws through the jelly of the egg. Within the process is a bundle of filaments which before induction are coiled up inside the sperm. The filament bundle exists in three stable states in the sperm. One of the states can be isolated in pure form. It is composed of only three proteins whose molecular weights (mol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
110
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 216 publications
(111 citation statements)
references
References 16 publications
1
110
0
Order By: Relevance
“…The microfilaments do not lie straight and parallel with each other in the false discharge acrosomal process as they do in the true discharge process, but instead are coiled around each other to produce a supercoil having a periodic structure in the electron microscope ( Figure 69). Formation of this supercoil may be related to the observation that the acrosomal process is ejected from the sperm in a very rapid wormscrew-like motion during the false dishcarge (Tilney, 1975). The corkscrew-like structure of the isolated acrosomal process is more evident in phase micrographs of the entire 50 ym process (Figure 70).…”
Section: Acrosomal Process Of Limulus Spermmentioning
confidence: 97%
See 4 more Smart Citations
“…The microfilaments do not lie straight and parallel with each other in the false discharge acrosomal process as they do in the true discharge process, but instead are coiled around each other to produce a supercoil having a periodic structure in the electron microscope ( Figure 69). Formation of this supercoil may be related to the observation that the acrosomal process is ejected from the sperm in a very rapid wormscrew-like motion during the false dishcarge (Tilney, 1975). The corkscrew-like structure of the isolated acrosomal process is more evident in phase micrographs of the entire 50 ym process (Figure 70).…”
Section: Acrosomal Process Of Limulus Spermmentioning
confidence: 97%
“…No attempt was made in this study to count the number of microfilaments in each process but Tilney (1975) has reported that the number of microfilaments ranges from 35 to 140 per process and varies along the length of a single process. The microfilaments do not lie straight and parallel with each other in the false discharge acrosomal process as they do in the true discharge process, but instead are coiled around each other to produce a supercoil having a periodic structure in the electron microscope ( Figure 69).…”
Section: Acrosomal Process Of Limulus Spermmentioning
confidence: 99%
See 3 more Smart Citations